Heterozygous mutations of HTRA1 gene in patients with familial cerebral small vessel disease. (6th August 2017) - Di Donato, Ilaria; Bianchi, Silvia; Gallus, Gian Nicola; Cerase, Alfonso; Taglia, Ilaria; Pescini, Francesca; Nannucci, Serena; Battisti, Carla; Inzitari, Domenico; Pantoni, Leonardo; Zini, Andrea; Federico, Antonio; et al.
Summary: Aims: Cerebral small vessel disease (SVD) is the leading cause of vascular dementia. Although the most of cases are sporadic, familial monogenic causes have been identified in a growing minority of patients. CADASIL, due to mutations of NOTCH3 gene, is the most common genetic SVD, and CARASIL, linked to HTRA1 gene mutations, is a rare but well known autosomal recessive SVD. Recently, also heterozygous HTRA1 mutations have been described in patients with familial SVD. To detect a genetic cause of familial SVD, we performed mutational analysis of HTRA1 gene in a large cohort of Italian NOTCH3 ‐negative patients. Methods: We recruited 142 NOTCH3 ‐negative patients and 160 healthy age‐matched controls. Additional control data were obtained from five pathogenicity prediction software. Results: Five different HTRA1 heterozygous mutations were detected in nine patients from five unrelated families. Clinical phenotype was typical of SVD, and the onset was presenile. Brain magnetic resonance imaging (MRI) showed a subcortical leukoencephalopathy, with involvement of the external and internal capsule, corpus callosum, and multiple lacunar infarcts. Cerebral microbleeds were also seen, while anterior temporal lobes involvement was not present. Conclusion: Our observation further supports the pathogenic role of the heterozygous HTRA1 mutations in familial SVD.